A construção do sentido - as inferências no conto “Missa do galo” de Machado de Assis - Cruz, Maria Cristina Fontes da (2019)
Reading should naturally imply in the process of understanding and producing inferences and not just stagnation of decoding. Marcuschi (1985) defines inference as a cognitive operation that provides new senses from others already achieved. This leaves a problem to be solved: to discover which pedagogical practices contribute effectively to assist the students in the construction of inferences in the literary text. The objective of this work is to produce a notebook of pedagogical orientations whose function will be to assist the teacher in the work of increasing the capacity of textual inferences with the students of the 8th year of Elementary School. Through the reading of the Mass story of Machado de Assis, we intend to collaborate with the teacher in order to improve his students 'abilities of inference and reading comprehension, as we hope that this work contributes to the improvement of students' performance in the different school disciplines and in the construction of school education as a whole. This work is relevant because it is in line with what is predicted in the eighth year Curricular Framework corresponding to the Portuguese Language course and, in this way, will help prepare students for the Brazil test, since this test works as a mechanism for evaluating the years of elementary school. In this research, we will use the concept of action research by Tripp (2005), the idea of reading Kleiman (2002), literary literary Cosson (2014), metacognition of Leffa (1996). The expected result of this research is to improve the reading ability of students involved in the project.